2017
DOI: 10.1016/j.stem.2017.03.008
|View full text |Cite|
|
Sign up to set email alerts
|

Gli1 + Mesenchymal Stromal Cells Are a Key Driver of Bone Marrow Fibrosis and an Important Cellular Therapeutic Target

Abstract: Bone marrow fibrosis (BMF) develops in various hematological and non-hematological conditions and is a central pathological feature of myelofibrosis. Effective cell-targeted therapeutics are needed, but the cellular origin of BMF remains elusive. Here, we show using genetic fate tracing in two murine models of BMF that Gli1 mesenchymal stromal cells (MSCs) are recruited from the endosteal and perivascular niche to become fibrosis-driving myofibroblasts in the bone marrow. Genetic ablation of Gli1 cells abolish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
239
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 211 publications
(258 citation statements)
references
References 43 publications
(55 reference statements)
10
239
2
Order By: Relevance
“…The identification of cells that drive the development of a fibrotic BM niche with its detrimental consequences for the maintenance of HSCs is a prerequisite for the development of novel targeted therapeutics. Two recent studies using state‐of‐the‐art techniques including genetic fate tracing in vivo , including our own work, provided evidence that LepR + and Gli1 + cells are key players in the initiation and progression of BM fibrosis 28, 37. Decker et al demonstrated that BM LepR + mesenchymal stromal lineage cells expand extensively and are fibrogenic in PMF 28.…”
Section: Stromal Cell Populations In Bm Fibrosismentioning
confidence: 76%
See 4 more Smart Citations
“…The identification of cells that drive the development of a fibrotic BM niche with its detrimental consequences for the maintenance of HSCs is a prerequisite for the development of novel targeted therapeutics. Two recent studies using state‐of‐the‐art techniques including genetic fate tracing in vivo , including our own work, provided evidence that LepR + and Gli1 + cells are key players in the initiation and progression of BM fibrosis 28, 37. Decker et al demonstrated that BM LepR + mesenchymal stromal lineage cells expand extensively and are fibrogenic in PMF 28.…”
Section: Stromal Cell Populations In Bm Fibrosismentioning
confidence: 76%
“…We have shown that Gli1 expression is significantly increased in stromal cells from MPN patients (Figure 3). Pharmacological targeting with the Gli inhibitor GANT61 inhibits Gli1 + cell expansion and myofibroblast differentiation, and attenuates fibrosis severity 37. These data thus provide a rationale for targeted therapy of Gli proteins in BM fibrosis, as monotherapy or combined therapy with other agents.…”
Section: Implications For the Therapy Of Bm Fibrosis – Treating The Dmentioning
confidence: 82%
See 3 more Smart Citations